(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
This article provides information on the technical indicators of the 4K channel, which is located in the guard farm District of the Bukhara region. A study of the technical condition of the channel revealed deficiencies and provided a summary and suggestions for eliminating existing deficiencies and improving the technical condition.